Characterization of early pozzolanic reaction of Calcium Hydroxide and Calcium Silicate Hydrate for Nanosilica modified cement paste. - J.Z., Chong; Norsuzailina, Mohamed Sutan; Ibrahim, Yakub (UNIMAS, 2022)
This study intends to investigate the early pozzolanic reaction of Nanosilica (nS) modified cement paste (NMCP) by the characterization technique of Calcium Hydroxide (CH) and Calcium Silicate Hydrate (C-S-H ) using Fourier Transform Infrared Spectroscopy (FT-IR). NMCP samples were prepared with water-binder ratio of 0.50. nS of 5-15nm particle size were used as 1%, 3% ,5% ,7% and 10% replacement of cement by weight. All samples were cured in the concrete laboratory at daily room temperature (T) and relative humidity (RH) in the range of 18-28oC and 65-90%, respectively. Powdered samples were prepared and tested at day 1,7,21 and 28. It was found that characterization technique used were able to give satisfactory qualitative indication of pozzolanic reactivity of NMCP by the presence and absence of C-S-H and C-H that can indicate which replacement has higher pozzolanicity. NMCP exhibited a higher pozzolanic reactivity compare to conventional cement paste by which cement performance was enhanced.